Methylation and gene expression differences between reproductive and sterile bumblebee workers - Marshall, Hollie (Evol Lett, 2019)
Phenotypic plasticity is the production of multiple phenotypes from a single genome and is notably observed in social insects. Multiple epigenetic mechanisms have been associated with social insect plasticity, with DNA methylation being explored to the greatest extent. DNA methylation is thought to play a role in caste determination in Apis mellifera, and other social insects, but there is limited knowledge on its role in other bee species. In this study, we analyzed whole genome bisulfite sequencing and RNA‐seq data sets from head tissue of reproductive and sterile castes of the eusocial bumblebee Bombus terrestris. We found that genome‐wide methylation in B. terrestris is similar to other holometabolous insects and does not differ between reproductive castes. We did, however, find differentially methylated genes between castes, which are enriched for multiple biological processes including reproduction. However, we found no relationship between differential methylation and differential gene expression or differential exon usage between castes. Our results also indicate high intercolony variation in methylation. These findings suggest that methylation is associated with caste differences but may serve an alternate function, other than direct caste determination in this species. This study provides the first insights into the nature of a bumblebee caste‐specific methylome as well as its interaction with gene expression and caste‐specific alternative splicing, providing greater understanding of the role of methylation in phenotypic plasticity within social bee species. Future experimental work is needed to determine the function of methylation and other epigenetic mechanisms in insects.